Defending the Trinity in the Reformed Palatinate: the Elohistae - Merkle, Benjamin (Oxford theology and religion monographs, 2015)
This study centres on Girolamo Zanchi's De Tribus Elohim (1572), placing it in its political and theological setting. De Tribus Elohim focussed on the grammatical peculiarity of the Hebrew word Elohim (God).